A Review of Factors Affecting Ganoderma Basal Stem Rot Disease Progress in Oil Palm - Nur Aliyah Jazuli; Assis Kamu; Chong, Khim Phin; Darmesah Gabda; Affendy Hassan; Idris Abu Seman; Ho, Chong Mun (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
In recent years, oil palm has grown on a major scale as it is a prominent commodity crop that contributes the most to almost every producing country’s gross domestic product (GDP). Nonetheless, existing threats such as the Ganoderma basal stem rot (BSR) disease have been deteriorating the oil palm plantations and suitable actions to overcome the issue are still being investigated. The BSR disease progression in oil palm is being studied using the disease progression through the plant disease triangle idea. This concept looks at all potential elements that could affect the transmission and development of the disease. The elements include pathogenic, with their mode of infection in each studied factor.